2017
DOI: 10.1038/ncomms15703
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous spatial distribution of the magnetic transition in an iron-rhodium thin film

Abstract: Monitoring a magnetic state using thermal or electrical activation is mandatory for the development of new magnetic devices, for instance in heat or electrically assisted magnetic recording or room-temperature memory resistor. Compounds such as FeRh, which undergoes a magnetic transition from an antiferromagnetic state to a ferromagnetic state around 100 °C, are thus highly desirable. However, the mechanisms involved in the transition are still under debate. Here we use in situ heating and cooling electron hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…It was shown, that the low temperature AFM phase is softer compared to the FM phase, as it was also demonstrated in a temperature-dependent EXAFS study performed by Wakisaka et al 31 In a recent work of Keavney et al, it could be shown by a combination of XMCD-PEEM and nano-XRD measurements, that the magnetostructural phase transition exhibits a defect-driven domain nucleation behaviour. 32 Similar effects of an inhomogeneous phase transition have been observed in a TEM study of Gatel et al, 33 where the film-surface and the film-substrate interface have a lower transition temperature than the centre of the film. Saidl et al 34 observed that the optical properties of different microscopic regions possess different transition temperatures leading to a distribution of transition temperatures T tr .…”
Section: Introductionsupporting
confidence: 66%
“…It was shown, that the low temperature AFM phase is softer compared to the FM phase, as it was also demonstrated in a temperature-dependent EXAFS study performed by Wakisaka et al 31 In a recent work of Keavney et al, it could be shown by a combination of XMCD-PEEM and nano-XRD measurements, that the magnetostructural phase transition exhibits a defect-driven domain nucleation behaviour. 32 Similar effects of an inhomogeneous phase transition have been observed in a TEM study of Gatel et al, 33 where the film-surface and the film-substrate interface have a lower transition temperature than the centre of the film. Saidl et al 34 observed that the optical properties of different microscopic regions possess different transition temperatures leading to a distribution of transition temperatures T tr .…”
Section: Introductionsupporting
confidence: 66%
“…The DPC image series of Figure 2 recorded the AF to FM transition during heating from 89°C to 200°C in the cross-sectional FeRh sample. The first small FM domain (~ 50 nm wide, ~ 20 nm high) nucleated at 89°C on the right-hand side of the FeRh / MgO interface, which is consistent with previous reports of inhomogeneous spatial distribution of the transition along the growth direction, where the transition initiates at the substrate interface 25 . This domain grows both laterally and upwards into the cross-section with temperature until 118°C, at which point another domain rapidly nucleates and grows on the left-hand side.…”
Section: Discussionsupporting
confidence: 92%
“…Fresnel imaging has revealed the FM domain structure in high quality 2D planar-view FeRh thin films produced for magnetic imaging within the TEM 24 . Electron holography has also exposed an inhomogeneous spatial distribution of the transition temperature along the growth direction in cross-sectional FeRh thin films, as well as a regular spacing of the nucleated FM domains 25 . However, preparation of cross-sectional thin film TEM lamellae is inherently destructive and shape anistropy dominates magnetically compared to its continuous film state.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was concluded that the existence of a FM surface layer is an is an intrinsic property of the FeRh(001) surface, rather than an artifact induced by capping layers or native surface oxide layers. Gatel et al [37] recently revisited the long standing question of the spatial distribution of magnetic patches in FeRh films. They used electron holography), a technique that allows quantitative mapping of the local magnetization and permits extraction of magnetic information across the entire film thickness with unrivaled spatial resolution.…”
Section: Epitaxial Strain In Ferh Thin Filmsmentioning
confidence: 99%
“…The color scale corresponds to the magnitude of the magnetization and the transition temperature is displayed by the white profile corresponding to magnetization of 0.75 T. (b) Amplitude image of the part of the FeRh layer used for the calculation. (c) Profiles of the transition temperature T* and the transition width T as a function of the position within the FeRh layer.Reproduced with permission from ref [37]…”
mentioning
confidence: 99%